PERAN INTERNAL AUDIT DALAM PENGUNGKAPAN KELEMAHAN MATERIAL (STUDI PADA BANK PERKREDITAN RAKYAT SE PROVINSI RIAU) - Febrian, Boy; Andreas, Andreas; M. Rasuli, M. Rasuli (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study aims to test empirically the effect of the role of internal audit on thedisclosure of material weaknesses in the Bank Perkreditan Rakyat of RiauProvince. The role of internal audit is divided into two namely, 1) Attributesinternal audit function (such as, competence, objectivity and investment), and 2)Fitness internal audit function (such as, grading, follow-up and coordination)tested the effect on the disclosure of material weaknesses.The questionnaire wassent to 111 internal auditors / Internal Audit Unit at a Bank Perkreditan Rakyat ofRiau Province. The participation rate amounted to 64.86% of respondents (72questionnaires returned) To test the hypothesis of the study, used Partial LeastSquare analysis using the program smartPLS 2.0 M3. .The results of this studyindicate that 1) attribute of the internal audit function (form, competence,objectivity and investment) influence on the material weakness disclosure, 2)internal audit function Activities (in the form of grading, follow-up andcoordination) to the disclosure of a material weakness.